Mobile Phone and Social Media Use of Homeless Youth in Denver, Colorado. Issue 2 (2nd April 2016) - Harpin, Scott; Davis, Jillian; Low, Hana; Gilroy, Christine
ABSTRACT: The purpose of this study was to investigate homeless youth mobile phone and social media use, to plan health promotion efforts. Nearly half (46.7%) of runaway/homeless youth in this sample ( n = 181) owned a mobile phone and a majority of those devices were smart phones. Ownership did not vary significantly by shelter location, though regular use of Facebook was more prevalent among those in housing programs or camping, than those living on the streets. Over 90% of youth in the sample reported using Facebook. Such media use might facilitate parent, family, and health provider communications with homeless youth.